2016
DOI: 10.1016/j.jval.2016.09.917
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of The Biosimilar Drug Policy in 10 Central Eastern European Countries

Abstract: flows and the required cost of capital, can be used to validate the price of the new drug from a narrow investor's perspective. The free cash flow represent the sales from the pharmaceuticals, and cash necessary for capital expenditures represent the costs for research & development (R&D) and marketing. The cost of capital refers to the opportunity cost of making a specific investment, which is the rate of return required to persuade the investor to make a given investment. Conclusion: We propose a policy appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…An illustrative study has provided evidence for this claim, and has shown that biologic drug availability varies substantially across countries and healthcare [ 14 ]. Other reports, and our own epidemiologic studies have shown that studies in a given demographic are especially warranted, as the projected estimates extrapolated from other studies often do not fall in line with first-hand evidence [ 14 , 15 , 16 , 17 , 18 , 19 ]. Moreover, the importance of this study is justified by the limited therapeutic armamentarium currently available in Poland.…”
Section: Introductionmentioning
confidence: 87%
“…An illustrative study has provided evidence for this claim, and has shown that biologic drug availability varies substantially across countries and healthcare [ 14 ]. Other reports, and our own epidemiologic studies have shown that studies in a given demographic are especially warranted, as the projected estimates extrapolated from other studies often do not fall in line with first-hand evidence [ 14 , 15 , 16 , 17 , 18 , 19 ]. Moreover, the importance of this study is justified by the limited therapeutic armamentarium currently available in Poland.…”
Section: Introductionmentioning
confidence: 87%
“…To respond to this political pressure several biologic medicines not meeting local cost-effective thresholds are reimbursed in lower income European countries, however various access restrictions are implemented to ensure the sustainability of health care financing [16]. These restrictions can influence prescribers, patients and manufacturers.…”
Section: Access Restrictions In Lower Income Countries With Limited Rmentioning
confidence: 99%